Model Pengembangan Pedagang Kaki Lima (PKL) Kuliner di Kota Singkawang - Jumhur, Jumhur (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
Even though small businesses are informal, they should always be fostered and facilitated in order to develop these businesses to be more independent in the future. Not to mention, the role of small businesses are very real, especially in employment and to alleviate poverty in Indonesia. There are several important aspects that have not been paid attention for the success of culinary street vendors, for instances organizational, financial, infrastructure, sanitation, environmental and marketing aspects. The main aim of this paper is to examine these aspects that affect the culinary street vendors which is the based on the development model of culinary street vendors that is going to be built in Singkawang city. The methodology used in this paper is descriptive research by combining quantitative and qualitative data analysis. The findings of this study show that street vendors culinary have role in developing local economy and empowering local people because they are able to employ the labors that cannot be employed in the formal sector. The developed models of street vendors culinary that is going to be implemented in Singkawang are dispersed and concentrated models.